Comparison of Academic Performances of Students among Various Ethnic Groups in Godawari Municipality - Giri, Gita (Janabhawana Research Journal, 2024)
Ethnic groups are fundamental unit of social system. Ethnicity is the source of the person’s self-actualization. This research is based on the perception of Nepali society that Brahmin/Chhetri and male students are higher education achievers. The study aimed to compare differences in academic performances of students among various ethnic groups (Brahmin/Chhetri vs non-Brahmin/Chhetri) and gender (male vs female). Data consisted examination result related with pre-board examination held in Jana Bhawana Campus since 2015 to 2022. Results of those students who have participated fully were considered. Data analysis was done using SPSS 20. Data are presented using descriptive statistics tools like percentage, mean and standard deviation. Academic performance results are presented by using percentage, t-tests and p-values. The finding showed that there are no differences in academic performance among Brahmin/Chhetri and non-Brahmin/Chhetri students whereas significance difference exists between male and female, where female students outperformed male. Awareness in education learning behavior and reducing in absenteeism can help in gaining academic success.